Support algorithm for blast furnace operation with optimal fuel consumption - Bernasowski, Mikolaj; Klimczyk, Arkadiusz; Stachura, Ryszard (Journal of Mining and Metallurgy, Section B: Metallurgy, 2019)
Fuel consumption in blast furnaces depends on many factors that are mainly conditioned by the technological level of a given blast furnace, the steel mill in which it operates, and the type and quality of ferrous feed, coke, and additional reducing agents. These are global factors which a furnace crew cannot control during operation. On the other hand, using their own experience and decision-making software, a crew can run a blast furnace with minimal fuel consumption under current batch and process conditions. The paper presents a model-based algorithm for optimizing the operation of blast furnaces to achieve the lowest fuel consumption. The algorithm allows the heat demands to be continuously calculated and highlights any wastage that could be reduced without affecting the stable operation of the blast furnace.
Keywords: Blast furnace fuel rate; Ironmaking; Direct reduction of wustite; Model-based control